A multi-channel MAC protocol with power control for multi-hop mobile ad hoc networks - Wu, SL; Tseng, YC; Lin, CY; Sheu, JP (My University, 2002)
In a mobile ad hoc network (MANET), one essential issue is Medium Access Control (MAC), which addresses how to utilize the radio spectrum efficiently and to resolve potential contention and collision among mobile hosts on using the medium. Existing works have been dedicated to using multiple channels and power control to improve the performance of MANET. In this paper, we investigate the possibility of bringing the concepts of power control and multi-channel medium access together in the MAC design problem in a MANET. Existing protocols only address one of these issues independently. The proposed protocol is characterized by the following features: (i) it follows an 'on-demand' style to assign channels to mobile hosts, (ii) the number of channels required is independent of the network topology and degree, (iii) it flexibly adapts to host mobility, (iv) no form of clock synchronization is required and (v) power control is used to exploit frequency reuse. Power control may also extend battery life and reduce signal interference, both of which are important in wireless communication. Through simulations, we demonstrate the advantage of our new protocol.